Effects of Walking Type and Speed on Oxygen Uptake and Fat Oxidation in College Students - Hye-Yeong Kim; Keun-Ok An; Sung-Sik Ko (Asian Society of Kinesiology, 2022)
OBJECTIVES The purpose of this study was to investigate the difference in oxygen uptake, fat oxidation rate, and fat oxidation during treadmill walking, depending on the type and speed of walking. METHODS Ten male college students randomly participated in the experiment under two conditions. Four types of exercise: normal walking, power walking, dumbbell walking, and sand walking, and three exercise intensity conditions: low-speed walking (40% VT), medium-speed walking (50% VT), and high-speed walking (60% VT). RESULTS Oxygen uptake was statistically significantly higher as walking speed increased (p<.001), and there was no statistically significant difference in walking type, but the interaction effect was statistically significant (p=.048). The fatty acid oxidation rate was statistically significantly lower as the walking speed increased (p<.001), and there was no significant difference in walking type, but the interaction effect was statistically significant (p=.008). There was a significant difference in the amount of fat burning according to the walking speed (p=.007), but there was no difference in the walking type, and there was no interaction effect. CONCLUSIONS Dumbbell walking and band walking increased oxygen intake under medium and high speed walking conditions, excluding low speed, compared to normal walking, and it is shown that normal walking and sand walking have an advantage in increasing the fat oxidation rate. In particular, considering the amount of fat oxidation, sand walking in all speed conditions is considered to be effective for weight loss, and it is suggested that it is necessary to investigate this later.